Debt Management Performance Assessment : Kingdom of Lesotho - World Bank (World Bank, Washington, DC, 2020)
At the request of the Minister of Finance of Lesotho, a joint World Bank -Macroeconomic and Financial Management Institute of Eastern and Southern Africa (MEFMI) mission visited Maseru, between July 2 to 6, 2018, to undertake a Debt Management Performance Assessment (DeMPA).The objective of the mission was to evaluate current performance against the DeMPA methodology, and to assess progress since 2012, when the first DeMPA was performed.The results of the evaluation, spanning the full range of debt management (DeM) functions, show limited progress. Compared to the previous DeMPA, the current assessment revealed only one upgrade related to the registry and management system for domestic debt of the CBL. Yet, additional actions to improve debt management in Lesotho are currently under discussion (i.e., approval of a new policy framework and public debt law), or have already started such as the publication of a debt statistical bulletin, undertaking of a Medium-Term Debt Strategy (MTDS) analytical exercise as the foundation for a Debt Management Strategy, and introduction of a Cash Management Unit.The assessment also revealed several downgrades associated to weaknesses in debt reporting to parliament, lack of regular information sharing between MoF - CBL and with market participants, as well as lack of secure storage and backup for the debt recording and management system of the MoF. Additional areas of improvement relate to, among others: i) fragmented legal framework; ii) lack of a loan guarantees’ framework; iii) preparation and approval of a formal Debt Management Strategy; iv) weak quality controls for data publication; v) quality of cash flow forecasts; vi) lack of policies and procedures for DeM operations; and, vii) completeness and timeliness of debt records.